2020
DOI: 10.36941/mjss-2020-0031
|View full text |Cite
|
Sign up to set email alerts
|

Parental Educational Level and Increase in Street Children in Calabar Metropolis, Cross River State, Nigeria

Abstract: This study examined the influence of parental educational level on the increase in street children in Calabar metropolis of Nigeria. Single speculation was defined to control the investigation. A writing survey was done dependent on the attribute under investigation. An approved four 16 ounces Likert scale questionnaire was utilized for assessment. The findings revealed that there is a significant influence of parental educational level on the increase in street children in Calabar Metropolis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Although the perspectives offered by various authors hold merit, many street children struggle to access these valuable opportunities. Edinyang et al (2020) strongly advocated for the involvement of parents and significant others in the educational lives of street children. Anthony and James (2019) asserted the importance of policymakers and education stakeholders implementing measures to effectively educate street children.…”
Section: Rehabilitation and Educationmentioning
confidence: 99%
“…Although the perspectives offered by various authors hold merit, many street children struggle to access these valuable opportunities. Edinyang et al (2020) strongly advocated for the involvement of parents and significant others in the educational lives of street children. Anthony and James (2019) asserted the importance of policymakers and education stakeholders implementing measures to effectively educate street children.…”
Section: Rehabilitation and Educationmentioning
confidence: 99%
“…From the field evidence collected, the study found that adults, particularly parents, strongly determine the development of a street child (Edinyang et al, 2020;Vergara del Solar et al, 2022). The behaviors of the adults or parents around children determine the children's behavior (Bellamy, 2001;Juhana & Nurhayati, 2023;Latif et al, 2023;Nurhayati, 2021;Ratningsih et al, 2021;Suharyat et al, 2023;Sulaimawan & Nurhayati, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The sad reality, however, remains that despite the existence of this legal document, the use of children as aids to street beggars especially visually challenged beggars has continued to thrive in both urban and rural communities in Nigeria. This to a large extent has been attributed to lack of knowledge on the content of legal documents protecting children in Nigeria (Ebigbo, 2003; Edinyang et al, 2020; Nnama‐Okechukwu & Erhumwunse, 2021; Okoye, 2011). Lack of knowledge has continued to promote the use of vulnerable children in illicit street vending activities hence the need for evidence‐based study from social workers to explore intervention method for a sustainable future.…”
Section: Introductionmentioning
confidence: 99%
“…Given the rising cases of child vulnerability and child work in both urban and rural communities in Nigeria, social work as a practice‐based profession need to rise up to the challenge to provide data and promote awareness on the legal framework protecting children in Nigeria using evidence‐based studies (Erhumwunse et al, 2021; Nnama‐Okechukwu & Erhumwunse, 2021). Various studies have explored the situation of street children in Nigeria (Bukoyo, 2015; Edinyang et al, 2020; Ebigbo, 2003; Ede & Kalu, 2018; Folami et al, 2018; Idowu et al, 2020). However, none of these studies have explored the lived experience of children who aid visually challenged street beggars and the factors associated with such venture.…”
Section: Introductionmentioning
confidence: 99%